Social participation and territorial governance: the challenges and contradictions of new public spaces based on the analysis of Paranã Valley, Goiás - Abdala, Bruno; Nunes, Juliana (Geografares, 2018)
This article aims to problematize the participatory institutions that have spread in Brazil during the last thirty years as the result of social participation’s valorization in the processes of elaboration of public policies. For that, we used the concepts of political space and territorial governance as operational concepts for the analysis of the territorial collegiate of the Paranã Valley, Goiás, our empirical study object. We aim to systematize the conceptual debate and highlight its relevance for the analysis of the challenges and contradictions of these participatory institutions in the Brazilian political-institutional context. Keywords: Political space, Territorial governance, Publicpolicy.